A prognostic score for patients with malignant pleural mesothelioma (MPM) receiving second-line immunotherapy or chemotherapy in the ETOP 9–15 PROMISE-meso phase III trial. (July 2022) - Banna, Giuseppe Luigi; Addeo, Alfredo; Zygoura, Panagiota; Tsourti, Zoi; Popat, Sanjay; Curioni-Fontecedro, Alessandra; Nadal, Ernest; Shah, Riyaz; Pope, Anthony; Fisher, Patricia; Spicer, James; Roy, Amy; et al.
Highlights: Malignant mesothelioma prognostic baseline clinical and laboratory parameters. Randomized trial on second line pembrolizumab or single agent chemotherapy. Stratified multivariate analysis. High systemic immune-inflammatory index and low hemoglobin associated with worse PFS. Definition of a mesothelioma risk score based on these two factors. Abstract: Introduction: Clinical and laboratory parameters associated with response for patients with advanced pre-treated malignant pleural mesothelioma (MPM) are lacking. We aimed to identify prognostic and predictive markers among patients with relapsed MPM who were randomised into the ETOP 9–15 PROMISE-meso phase III trial, evaluating pembrolizumab and chemotherapy. Methods: Baseline clinical and laboratory parameters were investigated for prognostic or predictive value on progression-free survival (PFS) and overall survival (OS) in a retrospective analysis, based on the full cohort of 144 MPM patients. These consisted of immune-inflammatory indexes (neutrophil–lymphocyte ratio [NLR], systemic immune-inflammatory index [SII], lactate dehydrogenase [LDH]) along with other already known prognostic baseline characteristics and laboratory values. Cut-offs were chosen independently of outcome. Based on Cox multivariable analysis for PFS in the whole cohort, a risk factor model was built to illustrate the prognostic stratification of patients by the combination of the derived independent prognostic factors, taking into account the EORTC score, a validated prognostic score in MPM. All models were stratified by histology and adjusted by treatment. Results: In the stratified multivariable analysis in the whole cohort, high SII (hazard ratio (HR) 2.06; 95%CI 1.39–3.05) and low haemoglobin (HR 1.62; 95%CI 1.06–2.50) were associated with worse PFS. Based on these two prognostic factors, a mesothelioma risk score (MRS) was constructed with three PFS risk prognosis categories: favourable, intermediate and poor with 0, 1 and 2 risk factors, respectively (corresponding percent of cohort: 24%, 34% and 42% and median PFS: 5.8, 4.2 and 2.1 months). The derived MRS stratified the prognosis for PFS and OS, overall and within each of the EORTC groups. No significant predictors of treatment benefit were identified. Conclusions: The proposed MRS is prognostic of patient outcome and it fine-tunes the prognosis of patients with pre-treated MPM alone or when used with the already established EORTC score.